New data on Salix anatolica (Salicaceae) endemic to Turkey - Terzi̇oğlu, Sali̇h; Serdar, Bedri̇; Karaköse, Mustafa; Coşkunçelebi̇, Kami̇l; Gültepe, Mutlu (Phytotaxa, 2014)
The endemic Anatolian willow, Salix anatolica (Salicaceae), was described based on solely female individuals in 2008. It was re-collected and the description was emended based on both male and female flower properties in the present study. Additionally, the pollen morphology, wood anatomical features and conservation status of S. anatolica are presented for the first time.